Gambaran Perkembangan Anak Berkebutuhan Khusus yang Diasuh oleh Orang Tua dengan Ekonomi Rendah - Novi Wahyu Winastuti,; Kartika Dian Pramesti,; Hasan Basri, (Happiness: Journal of Psychology and Islamic Science, 2022)
Children with special needs are children who require special treatment and assistance from both parents and experts. However, not all parents have the economic sufficiency to accompany their children. Therefore, researchers are interested in examining the description of the development of children with special needs who are cared for by parents with low economic conditions. The subjects of this study were 6 parents and children with special needs who have an age range of 8-11 years or equivalent to elementary school age. This study uses interview and observation techniques. The results of the study reveal that children who are cared for by parents who have a low economy can also develop optimally according to their respective conditions. The characteristics in the development of each child also cannot be separated from the way of parenting. And more in line with the development where the parents are and the extent of the parents' efforts in raising children. Parenting does not have to be accompanied by complete facilities but rather the right facilities so that children can grow up to be independent individuals. Attention, unyielding and active parents are also ways for children to develop optimally. In addition, the personality and beliefs of parents also affect how parents take care of them. Because if parents have personalities who are able to understand their children and have confidence from within, not just words, then parents will be able to raise children appropriately.